Evangelical Christian Baptists of Georgia : The History and Transformation of a Free Church Tradition - Sonġulašvili, Malxaz, 1963- (Book collections on Project MUSE., 2015)
Malkhaz Songulashvili, former Archbishop of the Evangelical Baptist Church of Georgia (EBCG), provides a pioneering, exacting, and sweeping history of Georgian Baptists. Utilizing archival sources in Georgian, Russian, German, and English-translating many of these crucial documents for the first time into English-he recounts the history of the EBCG from its formation in 1867 to the present. While the particular story of Georgian Baptists merits telling in its own right, and not simply as a feature of Russian religious life, Songulashvili employs Georgian Baptists as a sustained case study on th.